Atomic layer deposition of palladium thin film from palladium (II) hexafluoroacetylacetonate and ozone reactant - Zou, Yiming (2022)
Palladium thin films have been grown by thermal atomic layer (ALD) process using Palladium (II) hexafluoroacetylacetonate (Pd(hfac)2) and O3 as the precursors without molecular hydrogen or formalin in a temperature range of 180–220 °C. The palladium films were deposited on sapphire (α-Al2O3, (0001)), silicon (Si, (111)) and silica (SiO2, (100)) substrates at a constant growth rate of about 0.25 Å per cycle. The metallic palladium films produced were highly uniform without fluorine contamination. The surface roughness was only 0.2 nm. The resistivity of the metallic palladium film at ∼25 nm in thickness deposited at 200 °C was around 63 μΩ cm. The morphology of Pd thin films on sapphire, silicon and silica surfaces revealed the island growth and these islands finally coalesced after applying 800 cycles. Thickness-controllable palladium films were obtained with shortened pulse time of both reactants (Pd(hfac)2 and ozone). Our work provides important guidelines for fabrication of metals by adjusting reaction parameters in thermal ALD process.